(untitled) - Boniface, Brian G. (Oxford, 2009)
Worldwide Destinations: The Geography of Travel and Tourism is a unique text that explores the demand, supply, organisational aspects and resources of every tourism destination in the world.
Keywords: Tourism,Travel,Du lịch